Transforming the field: the role of academic health centers in promoting and sustaining equity based community engaged research - Sanchez-Youngman, Shannon; Adsul, Prajakta; Gonzales, Amber; Dickson, Elizabeth; Myers, Katie; Alaniz, Christina; Wallerstein, Nina (Frontiers in Public Health, 2023)
Community-Based Participatory Research (CBPR) and Community Engaged Research (CEnR) are key to promoting community and patient engagement in actionable evidence-based strategies to improve research for health equity. Rapid growth of CBPR/CEnR research projects have led to the broad adoption of partnering principles in community-academic partnerships and among some health and academic organizations. Yet, transformation of principles into best practices that foster trust, shared power, and equity outcomes still remain fragmented, are dependent on individuals with long term projects, or are non-existent. This paper describes how we designed our Engage for Equity PLUS intervention that leverages the leadership and membership of champion teams (including community-engaged faculty, community partners and patient advocates) to improve organizational policies and practices to support equity based CBPR/CEnR. This article describes the feasibility and preliminary findings from engaging champion teams from three very different academic health centers. We reflect on the learnings from Engage for Equity PLUS; the adaptation of the intervention design and implementation, including the development of a new institutional assessment using mixed research methods; and our organizational theory of change. In summary, our design and preliminary data from the three academic health centers provide support for new attention to the role of institutional practices and processes needed to sustain equity-based patient and community-engaged research and CBPR and transform the field.